2008
DOI: 10.4028/www.scientific.net/msf.584-586.9
|View full text |Cite
|
Sign up to set email alerts
|

R&D of NanoSPD Materials in Ufa via International Cooperation

Abstract: This report presents main achievements of international R&D activities of the Institute of Physics of Advanced Materials of Ufa State Aviation Technical University (Ufa, Russia) with a special attention to the innovative potential of nanostructured metals and alloys produced by severe plastic deformation techniques. Several examples of the first promising applications of bulk nanostructured materials as well as potential competing technologies are considered and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These properties suggest the obvious applications of UFG metals in high performance, lightweight components [14] but also in technological processes such as low temperature/high strain rate superplastic forming [15]. Other applications just take advantage of the small grain size and the increased amount of grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…These properties suggest the obvious applications of UFG metals in high performance, lightweight components [14] but also in technological processes such as low temperature/high strain rate superplastic forming [15]. Other applications just take advantage of the small grain size and the increased amount of grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…A different situation exists in the sports equipment industry, where performance is sometimes more important than cost. Therefore, initial attempts have been made to use UFG metals in high-performance bicycles (Reshetnikova et al , 2008) and in the faceplate of a golf club head (Safi ullin et al , 2009). The next few examples refer to advantages of UFG metals other than high strength; high strength may still be desirable, but it is not the main reason for using UFG metals in these applications.…”
Section: Structural Elementsmentioning
confidence: 99%
“…For example, a UFG Ti axle for the bottom bracket of a bicycle was 27% lighter than the original part made of CG Ti and 62% lighter than the same part made of a stainless steel. 21 Since the UFG part was also stronger, its life was substantially extended. An interesting opportunity opens up for UFG magnesium, which is one of the materials being considered for dissolvable cardiovascular stents.…”
Section: Applications Of Ufg Metalsmentioning
confidence: 99%
“…The first commercial application has been reported by a Czech company, Timplant, which makes UFG titanium dental screws. 21 The good mechanical properties of the material enable reduction of the screw diameter from 3.5 to 2.4 mm, making it more appropriate for front teeth and dental implants for children. Some studies have shown that in the case of UFG metals the bone integration rate is up to 20 times faster than that for conventional metals; patients should experience shorter post-surgery healing times and more reliable integration of these new implants into their body.…”
Section: Applications Of Ufg Metalsmentioning
confidence: 99%